2007
DOI: 10.2166/wst.2007.474
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and sequencing membrane bioreactors applied to food industry effluent treatment

Abstract: This work focuses on the performances of two immersed membrane bioreactors used for the treatment of easily biodegradable organic matter present in food industry effluents, for the purpose of water reuse. Two reactor functioning modes (continuous and sequencing) were compared in terms of organic carbon removal and of membrane permeability. For each working mode, pollutant removal was very high, treated water quality presented a low COD concentration (< 125 mg x L(-1)), no solids in suspension and low turbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Excellent MBR permeate quality with removal efficiency for turbidity, COD, BOD 5 , TN, NH 4 , TP and fecal coliforms found to be 98%, 85%, 94%, 63%, 72%, 19% and 99% respectively. Pilot-scale continuous and sequencing MBR for the treatment of high concentrations of organic matter present in food industry effluents showed COD concentrations of <125 mg/L, turbidity of <0.5 NTU, and zero suspended solids could be achieved in the treated effluent with this technology (Lobos et al, 2007).…”
Section: Treatment Technologiesmentioning
confidence: 96%
“…Excellent MBR permeate quality with removal efficiency for turbidity, COD, BOD 5 , TN, NH 4 , TP and fecal coliforms found to be 98%, 85%, 94%, 63%, 72%, 19% and 99% respectively. Pilot-scale continuous and sequencing MBR for the treatment of high concentrations of organic matter present in food industry effluents showed COD concentrations of <125 mg/L, turbidity of <0.5 NTU, and zero suspended solids could be achieved in the treated effluent with this technology (Lobos et al, 2007).…”
Section: Treatment Technologiesmentioning
confidence: 96%
“…A literature review reveals that the percentage removal of COD (or removal rates) achieved in this study are among the highest reported compared to previous studies where aerobic microbiological treatment processes were used in different suspended or attached systems (conventional activated sludge: up to 92.2% [48] and 50% [9], sequencing batch reactor: up to 95% [52], jet-loop-activated sludge reactor: 80%-90% [47,53], rotating biological contactor: 23%-43% [54,55], aerobic lagoons: 91% [56], fixed-bed biofilm reactor: up to 91% [14], biological sand filter: up to 98% [57], membranes: up to 97% [2,[58][59][60][61]). Although the most efficient aerobic biological process appears to be membrane application (where higher COD removal rates are achieved at shorter hydraulic retention times, and simultaneously exhibit stable operation under various organic loadings), these reactors present significant disadvantages such as high capital and operating costs, membrane fouling and difficulty in dewatering the produced waste sludge [16].…”
Section: Pilot-scale Trickling Filter Experimentsmentioning
confidence: 99%
“…According to the results of a study conducted by Lobos et al , SBMBRs exhibited higher membrane fouling rates compared with continues mode membrane bioreactors (MBRs). Applying higher fluxes due to the intermittent effluent discharge (batch filtration mode) is accounted as a reason for the higher fouling rate in SBMBRs . On the other hand, during the filtration phase in SBMBR systems, the hydraulic head decreases depend upon the volumetric exchange ratio (VER) adopted.…”
Section: Introductionmentioning
confidence: 99%